PENGARUH LEVERAGE, UKURAN PERUSAHAAN, INVENTORY INTENSITY, CAPITAL INTENSITY RATIO, SALES GROWTH DAN KOMISARIS INDEPENDEN TERHADAP TAX AVOIDANCE (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2016) - Furi, Gradini Diandra; Hardi, Hardi; Rusli, Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The purpose of this research is to examine the effectof leverage, size, inventory intensity, capital intensity ratio, sales growth, and independent commissioner on tax avoidance. The population is all manufacturing companies that listed in the Indonesia Stock Exchange Periode 2014-2016. The number of samples is 23 companies that are determined by purposive sampling method. Data analysis techniques used in this research was multiple linear regression analysis using Statistical Product and Service Solution (SPSS) version 25.0 for Windows as data processing software program. The result of this research show leverage, size, sales growth, and independent commissioner have an effect on tax avoidance, while inventory intensity and capital intensity ratio does not have an effect on tax avoidance. Based on calculation of coefficient determination (R2 ) was 0.234. Leverage, size, inventory intensity, capital intensity ratio, sales growth, and independent commissioner on tax avoidance simultaneously giving effect was 23,4%. While the remaining 76,6% is influenced by other independent variable that are nor observed in this research.Keywords : Leverage, Size, Inventory Intensity, Capital Intensity Ratio, Sales Growth, Independent Commissioner, and Tax Avoidance.